Carbon Monoxide and Air Quality Monitoring System with MATLAB GUI for Smart Home Application - Mat Jenur, Saiful Rahim; Zainal, Mohd Shamian; Hamzah, Shipun Anuar; Ramli, Khairun Nidzam; Adon, Mohamad Nazib; Lias, Jais; Md Som, Mohamad; Mustapa, Mohammad Sukri; Nordin, Shahilah (Progress in Engineering Application and Technology, 2020)
Carbon monoxide and air quality monitoring system is the practical technique to measure the carbon monoxide level as well as to monitor the air quality in a real time. The system will close down dangerous home appliances that potentially leaking the CO gas and might cause levels high enough to result in CO poisoning. The sensor will be installed at the potential spot and detect the presence of the gas. The sensor will send the data to the microcontroller to be processed and the microcontroller will execute the command action. MATLAB GUI is used to communicate with the microcontroller. By using MATLAB GUI, the critical level can be changed to safe without any hardware modification of the device. If sensors reading exceed the critical level or set point, MATLAB will send signal to the microcontroller to switch on the alarm, switch off the power supply equipment, and turn on the exhaust fan as well as opening the windows for ventilation purposes. Therefore, this project is a new method on carbon monoxide (CO) gas detection and air quality monitoring systems.